The trend towards vocational education and its relation to vocational awareness among the ninth grade students in Lattakia Governorate (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims at identifying the trend towards vocational education and its relation to vocational awareness among the ninth grade students in Lattakia Governorate, and the impact of sex variables and the continuation of school and place of residence in it. In order to achieve the research objectives, the analytical descriptive method was used by designing the first two scales to measure the trend toward vocational education and the second to identify the degree of professional awareness, The research sample consisted of 287 students from the ninth grade in Lattakia Governorate. The research reached the following results: - The trend toward vocational education among the ninth grade students in Lattakia governorate was negative, with an average of 2.39) and a relative weight of (47.8)%.) -The degree of vocational awareness among the ninth grade students in Lattakia governorate was average, with an average of 2.67) and a relative weight of( 53.4)%.) -There were statistically significant differences between the mean scores of the responses of the research sample on the measure of the trend towards vocational education according to the sex variable, in favor of males. -There were no statistically significant differences between the mean scores of the responses of the research sample on the measure of the trend towards vocational education according to the variables of the school (general, special) and place of residence (city, rural).